Identification of MUC5B as a lymph node metastasis-associated gene in lung adenocarcinoma through integrated transcriptomic and machine learning approaches - Song, Weijian; Yang, Qian; Du, Minjun; Wei, Jiacong; Zhou, Boxuan; Shi, Jianwei; Liang, Linchuan; Liu, Zixu; Liang, Mei; Li, Mianyang; Gao, Yushun (Frontiers in Immunology, 2025)
BackgroundLung adenocarcinoma (LUAD) is the most prevalent subtype of lung cancer, with lymph node metastasis serving as a key prognostic factor. MUC5B, a member of the mucin family, has been implicated in the progression of various cancers, yet its specific role in LUAD metastasis remains underexplored. This study aimed to investigate the role of MUC5B in LUAD progression and its potential as a biomarker for lymph node metastasis.MethodsWe integrated TCGA data, single-cell RNA-seq, and machine learning (LASSO, SVM-RFE) to identify MUC5B and associated metastatic markers. A 13-gene predictive model was constructed and validated using ROC analysis. Immunohistochemical staining confirmed the expression of MUC5B in the clinical case samples (n=65). In vitro experiments were performed using MUC5B-knockdown LUAD cell lines (A549, H1975) to assess changes in proliferation, migration, invasion, and colony formation. RNA sequencing was conducted to explore downstream molecular changes following MUC5B depletion.ResultsMUC5B was significantly upregulated in LUAD with lymph node metastasis and associated with poor overall and progression-free survival. Knockdown of MUC5B suppressed LUAD cell proliferation, migration, and invasion. The 13-gene model showed high predictive accuracy (AUC > 0.9) for lymph node metastasis. GSVA analysis revealed most model genes correlated positively with Th2 cells and negatively with mast cells, type II interferons. Transcriptomic profiling revealed that MUC5B depletion led to significant downregulation of GINS1, GINS2, and GINS4—core components of the DNA replication GINS complex—suggesting a regulatory axis between MUC5B and cell cycle progression. Enrichment analyses further indicated that MUC5B promotes LUAD metastasis via pathways involved in DNA replication, cell cycle, and metabolic reprogramming.ConclusionMUC5B facilitates LUAD lymph node metastasis, potentially by regulating the GINS complex and promoting oncogenic signaling. These findings highlight MUC5B as a promising biomarker and therapeutic target for advanced LUAD.